Competitive formation of spiro and ansa derivatives in the reactions of tetrafluorobutane-1,4-diol with hexachlorocyclotriphosphazene: A comparison with butane-1,4-diol - Besli, S; Coles, SJ; Davies, DB; Eaton, RJ; Kiliç, A; Shaw, RA (Pergamon-Elsevier Science Ltd, 2006)
Reaction of hexachlorocyclotriphosphazene, N3P3Cl6 (1), in two stoichiometries (1:1.2 and 1: 3) with the sodium derivative of the fluorinated diol, 2,2,3,3-tetrafluorobutane-1,4-diol (2), in THF solution at room temperature afforded six products, whose structures have been characterized by X-ray crystallography and H-1, F-19 and P-31 NMR spectroscopy: the mono-spiro compound, N3P3Cl4(OCH2CF2CF2CH2O) (3), its ansa isomer (4), a di-spiro derivative N3P3Cl2(OCH2CF2CF2CH2O)(2) (5), its spiro-ansa (6) and non-gem cis bis-ansa (7) isomers and a tri-spiro compound N3P3(OCH2CF2CF2CH2O)(3) (8). The tri-spiro derivative 8 was also formed in the reaction of the ansa compound 4 with diol (2) in a 1:3 ratio in THF at room temperature. The reactions of I with step-wise additions of 2 were also investigated at low temperature (-78 degrees C) to give the same range of products as at room temperature. The results of all reactions are compared with previous work on the reactions of I with butane-1,4-diol/pyridine mixtures and with the reaction of hexafluorocyclotriphosphazene, N3P3F6 (9), with the silyl derivative of the diol (2), (Me3SiOCH2CF2)(2), in a 1:0.4 mole ratio in the same solvent, THF. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: cyclophosphazenes; crystal structure; spiro; ansa; tetrafluorobutane-1,4-dioxy derivatives